1987
DOI: 10.5144/0256-4947.1987.323
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stroke and Heat Exhaustion in Pilgrims Performing the Haj (Annual Pilgrimage) in Saudi Arabia

Abstract: Heat stroke and heat exhaustion are not common problems among Saudi Arabians. They are, however, of significance in pilgrims from other parts of the world during Haj season, which varies according to the lunar calendar year. In recent years, Haj has coincided with the summer months of July and August. The temperatures during Haj reach an average high of 54°C (130°F). Lack of protection and precautionary measures is the primary reason for the high number of heat-stroke and heat-exhaustion cases among the pilgri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…27 The incidence of heatstroke is variable and is probably underestimated, ranging from 17.6 to 250 cases/100,000 population, depending on seasonal and geographical distribution. 28,29 However, there has recently been a marked increase thought to be associated in part with increased ambient temperature. Heat-related mortality rate is high and ranges between 33% and 80% where terminal events include shock, arrhythmias, myocardial infarction, renal failure and various neurological dysfunctions.…”
Section: Physiologymentioning
confidence: 99%
“…27 The incidence of heatstroke is variable and is probably underestimated, ranging from 17.6 to 250 cases/100,000 population, depending on seasonal and geographical distribution. 28,29 However, there has recently been a marked increase thought to be associated in part with increased ambient temperature. Heat-related mortality rate is high and ranges between 33% and 80% where terminal events include shock, arrhythmias, myocardial infarction, renal failure and various neurological dysfunctions.…”
Section: Physiologymentioning
confidence: 99%
“…35 During strenuous physical activity, body temperature increases in healthy persons, but as metabolic processes and/or environmental conditions exceed cardiovascular and central nervous system compensation, hyperthermia (T core > 40°C) ensues 13 and the risk of EHS increases. 10 Temperatures as high as 46.5°C (116°F) have been reported in patients who have recovered from heat stroke, 36 but survival at such an extreme T core is rare. The severity of tissue injury due to hyperthermia depends on the critical thermal maximum, 37 defined as the maximum intensity and duration of tissue heating before cellular death occurs.…”
Section: Hyperthermiamentioning
confidence: 99%
“…A review of the effect of warm weather showed a strong correlation between high temperatures or humidity and the use of medical care during Hajj more than 1000 deaths from heatstroke in a few days and more than 18 000 people needing treatment in emergency departments for heat exhaustion. 58 Heat-related mortality and morbidity are preventable; the risk of heat-related death is increased with old age and pre-existing illnesses, particularly cardiovascular, pulmonary, and psychiatric disorders. 59 Non infectious related illness are preventable like stampedes by crowd management and control, grouping and scheduling pilgrims, changes in the construction of the transport system and video monitoring of pilgrims lead to no stampedes since 2006.…”
Section: Fire Incidents In Hajjmentioning
confidence: 99%